2013
DOI: 10.1111/exd.12161
|View full text |Cite
|
Sign up to set email alerts
|

miR‐155 is involved in tumor progression of mycosis fungoides

Abstract: Biopsy specimens from 23 early stage and 19 tumorstage mycosis fungoides (MF) patients were evaluated for miR-155 expression by real-time qualitative PCR and compared with 15 biopsy specimens from patients with T-cell-rich inflammatory skin diseases. Significant upregulation of miR-155 was found in MF tumors compared with both early-stage MF lesions and controls. There was no difference in miR-155 expression between early-stage and inflammatory dermatoses. Using laser capture microdissection, it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
3
49
1
Order By: Relevance
“…The usefulness of some CTCL-related microRNAs as specific diagnostic or prognostic markers has been postulated and their potential role as promising targets has been proposed (Kopp et al, 2013a;Moyal et al, 2013;Schneider et al, 2012;Maj et al, 2012;Manfè et al, 2012;Manfè et al, 2013;McGirt et al, 2014;Ito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of some CTCL-related microRNAs as specific diagnostic or prognostic markers has been postulated and their potential role as promising targets has been proposed (Kopp et al, 2013a;Moyal et al, 2013;Schneider et al, 2012;Maj et al, 2012;Manfè et al, 2012;Manfè et al, 2013;McGirt et al, 2014;Ito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that miR‐155, miR‐92a, miR‐93 and miR‐326 are found to be overexpressed in MF compared with inflammatory skin diseases. In addition, higher expression levels of miR‐155 correlate with the progression of MF . In folliculotropic MF, the expression levels of miR‐155, miR‐223, miR‐34a, miR‐181a and miR‐93‐5p are upregulated, while the expression levels of miR‐34a, miR‐181a, miR‐181b, miR‐93‐5p and miR‐326 are overexpressed in MF with the large cell transformation (Fig.…”
Section: Pathogenetic Progressmentioning
confidence: 90%
“… in APMIS. Recently, miR‐155 expression was associated with severe disease . As IL‐15 expression in situ was also associated with severe disease, it is possibly that the correlation between miR‐155 expression and severe disease is a reflection of a specific cytokine environment with high levels of IL‐15, which in turn stimulates miR‐155 expression.…”
Section: Mini‐reviewmentioning
confidence: 99%